Sleep Disorders In Children With Epilepsy And Factors Affecting It - Praevilia M Salendu; Dwi Putro Widodo; Rini Sekartini (Jurnal Health Sains, 2023)
Background: Sleep disorders often occur in epilepsy with diverse properties and complex etiologies. Epilepsy causes sleep disorders that result in decreased quality of life. The purpose of this study was to determine the prevalence of sleep disorders in children with epilepsy as well as risk factors that influence sleep disorders in children with epilepsy.Research Methods: Analytical research with cross sectional approach. The research site at the Kiara Children's Polyclinic at Cipto Mangunkusumo Jakarta Hospital involved 99 subjects suffering from epilepsy. Determination of the sample using consecutive sampling. Data analysis used chi square test and logistic regression.Results: In the study of 99 subjects, the highest age range was 7 - 12 years (46.5%), women (50.5%) and men (49.5%). Common types of seizures (64.6%). The frequency of seizures per month ≥ 5 times (15.2%), the frequency of seizures <5 times (28.3%) and never had seizures (56.5%). Politerapi (63.6%) and the use of non-benzodiazepine drugs (88.9%). Intractable epilepsy (22.2%), cerebral palsy (28.3%) and abnormal EEG (51.5%). The prevalence of sleep disorders is 71.7% and the most common types of sleep disorders are disorders starting and maintaining sleep (62%). There was a relationship between seizure type, polytherapy, OAE type, intractable epilepsy, cerebral palsy and EEG images with sleep disorders in children with epilepsy (p <0.005).Conclusion: the prevalence of sleep disorders at 71.7% with factors that affect sleep disorders in children with epilepsy such as; generalized seizures, polytherapy, non-benzodiazepine drugs, intractable epilepsy, cerebral palsy and abnormal EEG images